An Investigation of the Students` Opinion on the Use of Digital Storytelling in Learning English - Yentri Anggeraini (ELT-Lectura, 2020)
Various kinds of technology tools and media can be used to facilitate the leaching and learning English in this era. One of them is digital storytelling. It is a multimedia text including images, audio, or video accompanied by a narrated soundtrack to tell a story or give information. It combines the functions of visual, verbal, and audio those are important for language comprehension and skills. This present study aimed at investigating the students` opinions on the use of digital storytelling in EFL classroom. The questionnaire and interview were distributed to 31 participants as the main data. The results indicated that 84% students like learning English through digital storytelling, 81% of them enjoy presenting and sharing their digital literacy, and 77% of them argue that digital storytelling can motivate them to read a lot. It can be derived that digital storytelling makes the students participate actively during the learning process, allows the students to work collaboratively, and provide the students to be digitally literate.